A SIMPLE LABORATORY EXPERIMENT WITH THERMOMETERS - Fuertes, J. Félix; López, José (IJRDO- Journal of Educational Research, 2017)
A simple laboratory experiment with alcohol-glass thermometers is proposed in order toemphasize the priority of work procedure in the laboratory tasks. Results allow us to introduce somequite interesting questions about the involved concepts, such as thermodynamic equilibrium or empiricaltemperature, and to obtain a general view about the evaluation of the importance of the measurementprocess in the operational way in scientific thinking. The explicit aim of the experiment is to measure thetemperature of a set of water samples with different amounts each. This is a simple but laborious taskwhich leads to undoubtedly questions of interest in a twofolded way: firstly, the difficulty on steppingfrom relationships between the measured values and their reliability and accuracy, representation,critical analysis and performances required, which are common tasks in any laboratory experiment;secondly, the difficulties raised from the conceptualization of the measured quantities, operationaldefinitions which are not currently taken into account in introductory physics courses. The comparisonof experimental results with the theoretical explanation allow us to combine both rationale methods,coupling the involved concepts to required manipulations and the proposal of new improvements.